1999
DOI: 10.1557/proc-608-721
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Radiation Resistance of a Mixed-Alkali Borosilicate Glass for High-Level Waste Vitrification

Abstract: Glasses related to those used for the vitrification of high-level waste (HLW) have been produced from the sodium-lithium borosilicate system. Their thermal and structural characteristics have been measured for a wide range of boron oxide contents (NBS series) and for a range of alkali oxide to boron oxide ratios, R, for several fixed silica to boron oxide ratios, K (ABS series). The NBS series of glasses was seen to exhibit a maximum in the glass transition temperature, Tg, and a minimum in the fraction of 4-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Peaks in the Raman spectra of all four systems have been identified by comparison with reports by Konijnendijk [36], Utegulov et al [25] and Bunker et al [26] 6 with those obtained by Roderick [43], the Dell [14] model and our previous study on Cs 2 O additions to MW [40]. For similar values of R, N 4 values for the four systems containing intermediate oxides are lower than both the prediction of the Dell model [14] and also the values observed for the systems composed of only group I (alkali) oxides CsMW [40,43]. Therefore, the simple argument of the removal of alkali as a chargecompensating cation for the intermediate species is insufficient to explain the reduction in the fraction of four-coordinated borate units.…”
Section: Raman Spectroscopymentioning
confidence: 58%
“…Peaks in the Raman spectra of all four systems have been identified by comparison with reports by Konijnendijk [36], Utegulov et al [25] and Bunker et al [26] 6 with those obtained by Roderick [43], the Dell [14] model and our previous study on Cs 2 O additions to MW [40]. For similar values of R, N 4 values for the four systems containing intermediate oxides are lower than both the prediction of the Dell model [14] and also the values observed for the systems composed of only group I (alkali) oxides CsMW [40,43]. Therefore, the simple argument of the removal of alkali as a chargecompensating cation for the intermediate species is insufficient to explain the reduction in the fraction of four-coordinated borate units.…”
Section: Raman Spectroscopymentioning
confidence: 58%
“…The compressional anisotropy of jadarite (derived along the three main crystallographic directions) is modest, with β a 0 : β b 0 : β c 0 = 1.23:1:1.23. Experiments devoted to the thermal behavior of jadarite will be part of a future study, which would unveil the T ‐stability of this mineral, the dehydroxylation mechanism and the occurrence of a derived sodium–lithium borosilicate‐glass, potentially usable in nuclear‐industry vitrification processes for high‐level wastes 44 Jadarite is expected to be a future commodity of Li and potentially B.…”
Section: Discussionmentioning
confidence: 99%
“…This being said, the presence of a third or more elements leads to the emergence of an immiscibility region and generates two phases by demixing the two networks. This means that the usual alkali-borosilicate glasses may be considered as a two phase system; one having an alkali-borate rich region and another silicon rich region [70,86,91]. The concept of separated phases is important in the frame of this study for two reasons, which concern…”
Section: Phase Separationmentioning
confidence: 99%
“…It is also worth remarking that knowledge of the glass transition temperature also provides an indirect tool to detect the existence of separated phases. Studies of Polyakova [85] and Roderick et al [91] have shown that an unmixed (i.e partially segregated) glass may exhibit one T g per phase, provided that the glass transition phenomena are distinct enough to be detected by the measuring system, there are no partial crystallization processes ongoing across the transition region, and the transition temperatures are well Borofloat N-ZK7 N-BK7 S-BSL7 T g (°C) 525 539 557 576 Table 3.1: Glass transition temperatures published by the manufacturers.…”
Section: Principle and Experimental Proceduresmentioning
confidence: 99%